ChemInform Abstract: A Silicon‐Position Dependent 6‐endo‐trig Cyclization During Tsuji—Trost Alkylation. Issue 13 (1st April 2014) - Agarwal, Jyoti; Commandeur, Claude; Malacria, Max; Thorimbert, Serge
Abstract The preparation of two silylated cyclohexenes by using a Tsuji—Trost palladium‐catalyzed cyclization is described.